Defender a ordem desordenando: o povo como sujeito da história e a questão do decoro na História Geral da Invasão dos Franceses de José Acúrsio das Neves (1810-1811) - Oliveira Júnior, José Alves de (2024)
The aim of this thesis is to analyze the representation of the people in the História Geral da Invasão dos Franceses (1810-1811) by José Acúrsio das Neves (1766-1834) and its effects on the representation of the hierarchical order of the Old Regime. Considering that the emergence of the people in the historian's political-military account is, above all, a modification in the seventeenth and eighteenth century ways of representing war in history. Such changes meant subversions in the decorum of historical art in its representation of the war event. In the 17th century, the writing of history was subject to the precepts of ancient rhetoric, with the idea of decorum as the basic premise for the selection and representation of themes in the narrative. Decorum established specific modes of treatment according to genres and hierarchies, determining appropriate rhetorical places for noble and common characters. Through this rhetorical procedure, military heroes, or “greats,” figured as central subjects in the accounts of the Restoration of 1640, because they were considered to lead the relevant events in politics and war and decide the fate of society. The writing of military history expressed its commitment to a certain conception of history and to the sharing of the sensible (Jacques Rancière) of that community. In the historiographical work of Acúrsio das Neves, the 17th-century staging of the war would be compromised by the subversion of decorum and the change in the discourse about the people, who were understood as the third estate or plebs. The transformation of the people into a theme or subject in the history of the Restoration of 1808 caused contradictions and disorders in the representative logic of society. By modifying the criteria for evaluating heroism, Acúrsio das Neves altered the relationship between the writing of history and the hierarchical constitution of the community, between the effects of words and the distribution of social bodies.